Effect of Different Tool Geometries in Friction Stir Welding of AA 2024-T3 using Design of Experiments - Al-Saadi, Moneer H.; Hussein, Sabah Khammass; Saad, Mursal Luaibi (Al-Nahrain Journal for Engineering Sciences, 2017)
In this work, Aluminum alloy (AA2024-T3) was welded by friction stir (FSW) method using different pin profile design types; straight cylinder, threaded cylinder, tapered cylinder hexagonal, square, and threaded taper. For each type, a flat and concave shoulder was used, as well as, the welding process was single and double. The results of mechanical tests are analyzed using design of experiments method (DOE). The best and weaken mechanical properties (tensile strength, bending force and hardness) are observed when the welding is achieved by hexagonal and straight cylinder pin profile respectively. A concave shoulder gave higher mechanical properties as compared with flat shoulder. The change in welding process type presented a sensible effect. Nugget zone hardness is higher than that of base metal for all specimens. The optimum hardness result is recorded by hexagonal pin with concave shoulder profile.